Peranan Badan Permusyawaratan Desa dalam Pemberdayaan Masyarakat di Sidoarjo - Lailiyah, Risaatul (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Abstract: This paper describes about the role of the Village Consultative Assembly in village of Jati, Banjar Bendo, and Sumput of Sidoarjo regency in empowering the community. Village Consultative Assembly is an institution that is the embodiment of democracy in a villageâs governance as an administrative element of the village. It functionates to set rules together with the Head of the village and accommodates the aspirations of the people. Village Consultative Assemblyâs role in empowering the community in the village of Jati and Sumput are less active. While, the Village Consultative Assembly in Banjar Bendo is very active. Beeing active or not active in carrying out their role lies on the implementation of the legislativeâs function that has been defined by Peraturan Pemerintah No. 72 year 2005 article 35 Juncto PERDA (Regional Legislation) of Sidoarjo No. 07 year 2006 article 12. The legislative duties and functions of the Village Consultative Assembly in Sidoarjo can not run optimally. This is indicated by the Village Consultative Assemblyâs less comprehensive in Jati and Sumput in framing the conventional regulations into the written rules. It is so since they got less technical assistance from the local government, especially in the field of legislation.Keywords: Role, village consultative assembly, Sidoarjo